Mortgaging guarantee between ( Al-Ahkam Al-Adliah) Magazine and Jordanian Civil Law - Al-So’ud, Suzan Abu; Ghaith, Majdi (Dirasat: Shari'a and Law Sciences, 2020)
Mortgaging is one of the most important contracts which was set to maintain the rights and to provide the owners on the others, and if any infringement or default of ‏ the parties to the contract or foreign mortgaged, it must be guaranteed; here lies the importance of this academic research. This research aims to develop the impact of the “Al Ahkam Al Adliah” Magazine on the Jordanian Civil Law, by studying Guaranteed mortgaged in both of them to devise سimilarities and differences between them, but before that, it studied mortgaging: Definition, sections and provisions. The researchers adopted the inductive, deductive and comparative approach in the research. The research has reached several results, including: the Jordanian civil law preserves the provisions of Islamic jurisprudence and “Al Ahkam Al Adliah” Magazine in its articles, and submit them to Western jurisprudence. The study recommended the need to conduct studies comparing the details of a civil contract in the Journal of judicial rulings and the Jordanian civil law. The two researchers also recommend Jordanian jurists to draw more in their studies from the Journal of judicial rulings and the details of its details when explaining the articles of the Jordanian civil code.